Creativity and the performing artist behind the mask - Thomson, Paula; Jaque, S. Victoria (Explorations in creativity research, 2017)
"Creativity and the Performing Artist: Behind the Mask synthesizes and integrates research in the field of creativity and the performing arts. Within the performing arts there are multiple specific domains of expertise, with domain-specific demands. This book examines the psychological nature of creativity in the performing arts. The book is organized into five sections. Section I discusses different forms of performing arts, the domains and talents of performers, and the experience of creativity within performing artists. Section II explores the neurobiology and physiology of creativity and flow. Section III covers the developmental trajectory of performing artists, including early attachment, parenting, play theories, personality, motivation, and training. Section IV examines emotional regulation and psychopathology in performing artists. Section V closes with issues of burnout, injury, and rehabilitation in performing artists."